Some Remarks About Deflation in the Case of Japan - Cossiga, Dott. Giovanni (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
The paper would like to examine the long stagnation of the Japanese economy facing the deflation, so trying to find a possible explanation, beyond the argument pointing into a possible liquidity trap. Afterwards, we are examining the course of the main variables from 1985 to present days, on the assumption that not efficacious correction of the boom excesses - concluded unsuccessfully the attempt of the Prime Minister Hashimoto to call into equilibrium the Japanese economic instability - would be responsible for the longtime-stagnant economy. The country in the nineties continued to grow at a slow pace, so that the first recession occurs only in 1998 in connection with the crisis in Southeast Asia. In other words, the correction of the excesses of the boom by means of a creative recession, Schumpeter model, did not take place. The economy has remained unstable. It is assumed in fact that by the early 2000s, within the endless flow of Keynesian interventions and liquidity to support the economy has not yielded the expected results. In contradiction occurred weakening economy and deflation. The increase in non-stop public debt and liquidity appear to have played a role of third wheel, between declining economic performance and price trend in deflation. Finally, through the econometric tools, the effects of excessive public debt on economic activity and deflation are also examined.